PENGEMBANGAN STRATEGI EKONOMI KREATIF DI KOTA PALANGKARAYA - Muhamad Yusuf (Dinamika : Jurnal Ilmiah Ilmu Administrasi Negara, 2023)
The creative economy is one of the new economic concepts that intensifies information and creativity as well as Human Resources (HR) as the most important factors of production. The development of a creative economy strategy can be carried out through five pillars in supporting the strength of the New Indonesia in 2025, such as supporting resources, industry or tourism, financing, marketing, technology and infrastructure. This research was conducted using an interactive qualitative approach. This research uses a descriptive approach based on the process of developing creative economic strategies in the city of Palangkaraya. The collection of research data through the process of interviews, observation and documentation. The selection of informants was carried out using a purposive sampling technique. Data analysis used interactive analysis which aimed to analyze in the first research and explanatory design to analyze in the second research. The results of research on the development of creative economic strategy development in the city of Palangkaraya through the five pillars generally still require several aspects to support industrial and tourism development activities ranging from capital, policies to human and natural resources owned and the expansion of production networks to disseminate and introduce industry and tourism that can compete with others.